ชุดกิจกรรมการเรียนการสอนเรื่องเมทริกซ์โดยใช้เครื่องคำนวณเชิงกราฟสำหรับนักเรียนชั้นมัธยมศึกษาปีที่ 4 - ทัสนะเมธี, ภุมริน; โสธะโร, สายัณห์ (Science Essence Journal, 2018)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อ 1) ศึกษาผลสัมฤทธิ์ทางการเรียนของนักเรียน 2) สร้างชุดกิจกรรมการเรียนการสอนให้มีประสิทธิภาพตามเกณฑ์ 80/80 3) ศึกษาความพึงพอใจของนักเรียนที่มีต่อชุดกิจกรรมการเรียนการสอน กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ เป็นนักเรียนชั้นมัธยมศึกษาปีที่ 4 โรงเรียนสตรีภูเก็ต อำเภอเมือง จังหวัดภูเก็ต ภาคเรียนที่ 2 ปีการศึกษา 2560 เป็นการสุ่มตัวอย่างแบบเกาะกลุ่ม จำนวน 41 คน ผู้วิจัยดำเนินการสอนด้วยชุดกิจกรรมการเรียนการสอนเรื่องเมทริกซ์โดยใช้เครื่องคำนวณเชิงกราฟที่ผู้วิจัยสร้างขึ้น ใช้เวลาสอน 16 ชั่วโมง เมื่อสิ้นสุดการสอนผู้วิจัยให้นักเรียนทำแบบทดสอบวัดผลสัมฤทธิ์ทางการเรียนเรื่องเมทริกซ์และแบบสอบถามวัดความพึงพอใจของนักเรียน ผลการวิจัยพบว่า นักเรียนชั้นมัธยมศึกษาปีที่ 4 มีความสามารถในการเรียนเรื่องเมทริกซ์ ด้วยชุดกิจกรรมการเรียนการสอนเรื่องเมทริกซ์โดยใช้เครื่องคำนวณเชิงกราฟ ที่ผู้วิจัยสร้างขึ้น ซึ่งสามารถผ่านเกณฑ์ได้มากกว่าร้อยละ 80 ของจำนวนนักเรียนทั้งหมดที่ระดับนัยสำคัญ .01 ชุดกิจกรรมการเรียนการสอนมีประสิทธิภาพ ( ) เท่ากับ 88.82/90.3 ซึ่งสูงกว่าเกณฑ์ 80/80 และนักเรียนกลุ่มตัวอย่างมีความพึงพอใจในการเรียนเรื่องเมทริกซ์โดยใช้เครื่องคำนวณเชิงกราฟอยู่ในระดับมาก - - - Instructional Activity Package on Matrices by Using Graphic Calculator for Matayomsuksa Four Students ABSTRACT The purposes of this research were 1) to study the student achievement of Matayomsuksa Four on Matrices; 2) to construct an instructional activity package which had an effectiveness criterion of 80/80, and 3) to evaluate the attitudes of students toward the instructional activity package. The study was preceded during the second semester of the 2017 academic year with Mathyomsuksa Four students at Satree Phuket School in Phuket, Thailand. Forty one students were selected as the experiment group using the cluster sampling approach. The researcher taught them totally sixteen hours. An achievement test was given to measure their performance on the matrices at the end of instruction. A questionnaire for investigating their attitudes was also distributed to them in order to find out their preference. After using instructional activity packages, the results revealed that there are more than eighty percent of the subjective students who performed better than seventy percent of the total score at .01 level of significance. This shows that the Mathayomsuksa Four students had the ability to learn with the matrices by using the instructional activity package created by the researcher. The implementation of the instructional activity package showed that the educational efficiency ( ) of the instructional activity packet was effective at 88.82/90.3, which higher than a predetermined threshold (80/80). In addition, the questionnaire results showed that they had a high level of positive attitudes on matrices in which the graphic calculator was included to teach them.